2001
DOI: 10.1379/1466-1268(2001)006<0049:hpmotc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 protects mitochondria of thermotolerant cells against apoptotic stimuli

Abstract: Enhanced cell survival and resistance to apoptosis during thermotolerance correlates with an increased expression of heat shock proteins (Hsps). Here we present additional evidence in support of the hypothesis that the induction of Hsp27 and Hsp72 during acquired thermotolerance in Jurkat T-lymphocytes prevents apoptosis. In thermotolerant cells, Hsp27 was shown to associate with the mitochondrial fraction, and inhibition of Hsp27 induction during thermotolerance in cells transfected with hsp27 antisense poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 50 publications
(64 reference statements)
4
87
0
9
Order By: Relevance
“…Hsp25 was reported previously (38) to be in the cytosol and nucleus. Recently, Hsp25 was identified in the mitochondria of mouse PC12 cells (39) and heat-shocked Jurkat T-lymphocytes (40). In our experiments, Hsp25 was barely detectable in liver mitochondria from control rats but increased greatly in both mitochondrial (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Hsp25 was reported previously (38) to be in the cytosol and nucleus. Recently, Hsp25 was identified in the mitochondria of mouse PC12 cells (39) and heat-shocked Jurkat T-lymphocytes (40). In our experiments, Hsp25 was barely detectable in liver mitochondria from control rats but increased greatly in both mitochondrial (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Overexpression of human Hsp27 and mouse Hsp25 protects mouse L929 fibroblasts against oxidative stress induced by H 2 O 2 and increases the activity of glucose-6-phosphate dehydrogenase, a regulator of antioxidant pathways (34). Inhibition of Hsp27 expression with hsp27 antisense also potentiates mitochondrial depolarization and cytochrome c release after apoptotic stimuli in Jurkat cells (40). In mice lacking heat shock transcription factor 1, cardiac Hsp25 expression is decreased; superoxide production is increased; mitochondrial proteins including adenine nucleotide translocator 1 are more oxidized, and isolated mitochondria are more sensitive to MPT induction by CaCl 2 (41).…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44] Increased expression of HSP27 serves to defend a cell against injury or death by acting as chaperones facilitating proper polypeptide folding and aberrant protein removal. [45][46][47] Furthermore, HSP27 is a potent anti-apoptotic protein and is a key stabilizer of the actin cytoskeleton; both of these cellular effects lead to increased resistance against cell death. [48][49][50] We previously showed that intrarenal injection of EGFP-huA 1 AR lentivirus in mice not only increased the HSP27 expression but also increased colocalization of HSP27 with F-actin in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The key element of the heat-activated apoptotic cascade is efflux from mitochondria of cytochrome c, which activates a cascade of caspases, including caspase-9 and caspase-3 (33,39,49), leading to execution of apoptosis ( Fig. 1).…”
Section: Cell Death and Survival Pathways Activated By Heat Shockmentioning
confidence: 99%